About the Experience of Death in Eda Ostrowska’s Poetry - Niesporek, Katarzyna (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
Eda Ostrowska is a poet who contemplates death of her life. In the words of Stefan Chwin from thebook Suicide as an Experience of Imagination, Ostrowska knows too much about the dark side of life,sees what she shouldn’t, strongly feels the pain and exceeds the designated limit of the risk. Ostrowska isrejected by society as a genuine stranger, the outsider still thinking about death. She has a strong awarenessof dying, obvious transience which she expresses not only in the poetry but also in the diary I Stand inFront of You in the Body Rain. Lonely, misunderstood by people Ostrowska is living, but constantly dying.Convinced of the value of being on the other side but not having the courage to end up with her life, shefinds narcotic alternative spaces which allow her to exist on the edge, to dice with death and life.